Non-surgical treatment of Achilles rupture: Does duration in functional weight bearing orthosis matter?. Issue 4 (December 2016) - Aujla, Randeep; Kumar, Amit; Bhatia, Maneesh
Highlights: A cohort study involving 88 patients who had acute Achilles tendon ruptures. They were splint into regimes of either 8 or 11 weeks. There was no difference in functional outcomes and complications between groups. A 8-week dynamic functional regime is satisfactory non-operative treatment. Abstract: Background: The treatment of acute Achilles tendon ruptures is continually being debated. The success of non-surgical regimes is now evident yet there remains a high rate of surgery in the United States of America and Scandinavia. Recent studies have investigated functional outcome rather than complication rates as primary outcome but the current data are still sparse. We aimed to investigate whether there is any difference in functional outcomes between two dynamic regimes of differing durations for acute Achilles tendon ruptures. Methods: The patients in the two groups were matched for age, gender, follow-up duration and mechanism of injury. Forty-four patients were managed in a regime of 11 weeks and another 44 patients for 8 weeks. Demographics, injury details, complications and functional outcome were recorded. The validated Achilles Tendon Rupture Score (ATRS) was used to assess functional outcomes. Minimum follow-up was 1 year. Results: The 11-week group had a mean age of 50.8 years (range: 27–80) with 36 (82%) males. The 8-week group had a mean age of 52.0 years (range: 32–77) with 36 (82%) males. The mean ATRS for the 11-week group was 76.0 (range: 8–100). The mean ATRS for the 8-week group was 76.1 (range: 30–100). There were no re-ruptures in the 11-week group and one in the 8-week group. There were three episodes of venous thromboembolism in the 11-week group and four in the 8-week group. Conclusion: A reduction in duration of dynamic rehabilitation for non-operative treatment of Achilles tendon rupture from 11 weeks to 8 weeks does not lead to a significant detriment in functional outcomes or complication rates.